2008
DOI: 10.1007/s00018-008-8065-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological manipulation of L-carnitine transport into L6 cells with stable overexpression of human OCTN2

Abstract: The high-affinity Na+-dependent carnitine transporter OCTN2 (SLC22A5) has a high renal expression and reabsorbs most filtered carnitine. To gain more insight into substrate specificity of OCTN2, we overexpressed hOCTN2 in L6 cells and characterized the structural requirements of substances acting as human OCTN2 (hOCTN2) inhibitors. A 1905-bp fragment containing the hOCTN2 complete coding sequence was introduced into the pWpiresGFP vector, and L6 cells were stably transduced using a lentiviral system. The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
1
18
0
2
Order By: Relevance
“…These prior genetic studies suggest that unintentional alteration of hOCTN2 function, for example by the use of drugs (3), can potentially lead to deleterious phenotypic changes in patients. Indeed, the principal metabolic abnormalities associated with excessive urinary carnitine loss in individuals with primary SCD are also observed following treatment with certain prescription drugs known to inhibit hOCTN2 function in vitro , such as verapamil (4). Few previous studies have identified a number of widely used anticancer drugs as inhibitors of hOCTN2, including actinomycin D (5) and vinblastine (6).…”
Section: Introductionmentioning
confidence: 99%
“…These prior genetic studies suggest that unintentional alteration of hOCTN2 function, for example by the use of drugs (3), can potentially lead to deleterious phenotypic changes in patients. Indeed, the principal metabolic abnormalities associated with excessive urinary carnitine loss in individuals with primary SCD are also observed following treatment with certain prescription drugs known to inhibit hOCTN2 function in vitro , such as verapamil (4). Few previous studies have identified a number of widely used anticancer drugs as inhibitors of hOCTN2, including actinomycin D (5) and vinblastine (6).…”
Section: Introductionmentioning
confidence: 99%
“…Both activities were also sensitive to pharmacologically important drugs, as verapamil and quinidine (Fig. 3), at concentrations known to inhibit OCTN2 [24,25].…”
Section: Resultsmentioning
confidence: 96%
“…3a, these cells accumulate carnitine and carnitine transport was diminished by 40% in the absence of Na, pointing to a substantial activity of Octn3 in neural cells. In order to further verify an involvement of Octn transporters in carnitine accumulation, its transport was measured in the presence of compounds known to inhibit carnitine transporters expressed in Xenopus laevis oocytes or mammalian cells [8,24,25]. Carnitine Na-dependent and Na-independent transport was inhibited by butyrobetaine, confirming activity of Octn2 and Octn3 [8].…”
Section: Resultsmentioning
confidence: 99%
“…Besides primary carnitine deficiency, which is caused by mutations in the gene coding for the renal carnitine carrier OCTN2 (organic cation/carnitine transporter No. 2) [4], there are secondary carnitine deficiency states, which are primarily caused by renal excretion of acylcarnitines [5,6], interactions of drugs or toxins with OCTN2 [7,8], or due to the removal of carnitine by hemodialysis [9]. While treatment with carnitine is life saving for patients with primary carnitine deficiency and can be associated with symptomatic relief in those with secondary deficiency, it is so far not clear whether other individuals could also profit from intake of supplemental carnitine.…”
Section: Introductionmentioning
confidence: 98%